The Effects of Academic Probation on College Success: Regression Discontinuity Evidence from Four Texas Universities - Jason M. Fletcher; Mansur Tokmouline (Institute of Labor Economics (IZA), 2017)
While nearly all colleges and universities in the United States use academic probation as a means to signal to students a need to improve performance, very little is known about the use of this designation and the programs that accompany it on college success. This paper uses a regression discontinuity approach to estimate the effects of these programs at four universities of varying selectivity in Texas. Results suggest that academic probation status following the first semester of college may serve as a short term "wake up call" to some students, in that second semester performance is improved. However, our findings also suggest that this short term boost in performance fades out over time and students who are on academic probation following their first semesters of college do not have higher rates of persistence or graduation. We also find important differential responses to academic probation based on pre-determined student characteristics as well as high school of origin. However none of the heterogeneous effects are consistent across universities, limiting the application of simple models of education standards.
Keywords: J24; I21; 330; academic probation; regression discontinuity; higher education